2014
DOI: 10.1007/s10488-014-0547-3
|View full text |Cite
|
Sign up to set email alerts
|

“You Might Lose Him Through the Cracks”: Clinicians’ Views on Discharge from Assertive Community Treatment

Abstract: Assertive Community Treatment (ACT) teams are increasingly interested in improving access to ACT through discharge of improved clients to less intensive mental health care services. We report results from a process evaluation of three teams in the VA's ACT program, Mental Health Intensive Case Management (MHICM), that began to implement discharge. MHICM clinicians (n=15) describe significant barriers to discharge. Clinicians support the concept of discharge but raise concerns about clients' future stability, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Several studies have found clinicians' perceptions of client-centeredness to conflict with their perceived need for coercion. In mental health contexts, diverse factors may encourage some degree of coercion including that clinicians often work in underresourced contexts where ideal 27 treatment is not available and work with individuals for whom risk-taking can result in serious consequences including homelessness or rehospitalization (Bromley, Mikesell, Armstrong & Young, 2014). While we also found such discordance between the need for both client-centeredness and coercion, it did not merely stem from beliefs that clinicians' knowledge is superior but appeared to equally arise from beliefs about clinicians' roles (cf.…”
Section: Role Of Epistemic Expertise In Managing Informationmentioning
confidence: 99%
“…Several studies have found clinicians' perceptions of client-centeredness to conflict with their perceived need for coercion. In mental health contexts, diverse factors may encourage some degree of coercion including that clinicians often work in underresourced contexts where ideal 27 treatment is not available and work with individuals for whom risk-taking can result in serious consequences including homelessness or rehospitalization (Bromley, Mikesell, Armstrong & Young, 2014). While we also found such discordance between the need for both client-centeredness and coercion, it did not merely stem from beliefs that clinicians' knowledge is superior but appeared to equally arise from beliefs about clinicians' roles (cf.…”
Section: Role Of Epistemic Expertise In Managing Informationmentioning
confidence: 99%
“…Although education has been shown to be effective in reducing stigma and improving staff capacity to manage service users, efforts to improve nurses’ and other clinicians’ attitudes and behaviours are most effective and sustainable when they also address extant beliefs, perceived or actual priorities and current practices (Bromley et al . , Gras et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Several initiatives have been implemented to improve the care and management of service users with medical co‐morbidity (Bromley et al . , Lally et al . , Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…ACT exits have been identified as both planned and voluntary, as well as, unplanned and involuntary exits. Planned, voluntary ACT service exits occur through achieving recovery and transferring to less intensive services, while involuntary unplanned exits from care are the result of service refusal or long-term institutionalization (i.e., jail or hospital/nursing home; Bromley et al, 2015Bromley et al, , 2017Chen & Herman, 2012;Finnerty et al, 2015;Mantzouranis et al, 2019). To date, there is limited published research of TIP and AMP!…”
Section: Young Adults Service Disengagementmentioning
confidence: 99%